Efektivitas Kontrol Metabolik terhadap Kualitas Hidup pada Anak dengan Diabetes Mellitus Tipe 1 - Amalia Dewi Ariyanti; Allenidekania Allenidekania (Journal of Telenursing (JOTING), 2021)
This study aims to identify the effectiveness of metabolic control on the quality of life of children with T1DM. The method used is an electronic database literature search through ScienceDirect, ProQuest, EBSCO, Scopus and Springer Link by reviewing the results of previous research from published articles. The results showed three articles related to the components of metabolic control, namely the use of CSII and MDI, Insulin Degludec (IDeg), the use of the telehealth system, and three articles related to the quality of life of children with T1DM. In conclusion, a better quality of life is associated with better metabolic control. Treatment adherence is crucial to achieving reasonable metabolic control and can be related to the quality of life. Keywords: Children, Type 1 Diabetes Mellitus, Metabolic Control, Quality of Life